(untitled) - Fant, Karl M. (Hoboken, N.J., 2007)
The Invocation Model of Process Expression argues that mathematics does not provide the most appropriate conceptual foundations for computer science, but, rather, that these foundations are a primary source of unnecessary complexity and confusion._ It supports that there is a more appropriate conceptual model that unifies forms of expression considered quite disparate and simplifies issues considered complex and intractable._ This book presents that this model of process expression is alternative theory of computer science that is both valid and practical.
Keywords: Computer science,Electronic data processing,Khoa học máy tính,Xử lý dữ liệu điện tử; Distributed processing,Xử lý phân bố